Central bank communications and financial market reactions in Nigeria - Uwatt B. Uwatt; Ada Tony Odu; Itodo Idoko Ahmed (West African Journal of Monetary and Economic Integration, 2024)
This study examines financial market reactions to policy communication of the Central Bank of Nigeria (CBN). Specifically, text mining techniques are employed to analyse the monetary policy communique of the CBN from February 2004 to May 2023 and to extract the sentiments and tones expressed by the communique. Thereafter, structural vector autoregressive (SVAR) models are used to evaluate the unique impacts of the tones and sentiments on the performance of the stock and foreign exchange markets. The findings reveal that the CBN uses more words in its communique during challenging periods and that most of the communique expressed positive sentiments using a dovish tone. This implies that the MPC is focused more on stimulating economic activity and spurring economic growth. Regarding the impact analyses, the findings reveal that the impact of the monetary policy shocks on stock market performance is amplified when the MPC communique expresses negative sentiments. In the foreign exchange market, the impact of the monetary policy shock is amplified and more persistent when positive sentiment is replaced with negative sentiment. In terms of tones, the findings indicate that when hawkish tones are used, a monetary policy shock has a larger impact on the all-share index and exchange rate. Given these findings, the study recommends the combination of negative sentiments and hawkish tones in the CBN's communications when it intends to influence financial market performance. It also recommends the tone-rate decision consistency to send clear signals to the financial markets.
Keywords: C32; E52; E58; G10; 330; Monetary policy communication; Financial markets; Text-mining; Tone; Sentiment